2013
DOI: 10.1016/j.msea.2013.04.071
|View full text |Cite
|
Sign up to set email alerts
|

Hot deformation behavior and workability characteristics of AZ91 magnesium alloy powder compacts—A study using processing map

Abstract: This study examined the hot deformation behavior and workability characteristics of AZ91 Mg alloy powder compacts by performing hot compression tests with a Gleeble 3800 machine. To this end, powder compacts with a relative green density of 93% were hot-compressed at temperatures ranging from 150 1Cto5001C and at true strain rates ranging from 0.001 s −1 to 10 s −1 . The true stress-true strain curves peaked at low strains, after which the flow stress increased slightly or remained constant. The work hardening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 37 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…That is because Al atoms can lead to a strong dragging effect on the dislocations which can reduce the mobility of dislocations, thereby making the deformation harder [ 36 ] and increasing the Q value. [ 37 ] The Q‐value in the AZ80 is about 190 kJ mol −1 [ 20,38 ] much higher than AZ80‐0.8wt%Y in this study. Adding yttrium to magnesium alloy can form Al 2 Y phase which reduces the continuous distribution of eutectic Mg 17 Al 12 phase.…”
Section: Resultsmentioning
confidence: 58%
“…That is because Al atoms can lead to a strong dragging effect on the dislocations which can reduce the mobility of dislocations, thereby making the deformation harder [ 36 ] and increasing the Q value. [ 37 ] The Q‐value in the AZ80 is about 190 kJ mol −1 [ 20,38 ] much higher than AZ80‐0.8wt%Y in this study. Adding yttrium to magnesium alloy can form Al 2 Y phase which reduces the continuous distribution of eutectic Mg 17 Al 12 phase.…”
Section: Resultsmentioning
confidence: 58%
“…Figure 15 shows the safe area of different materials at strain of 0.5. It can be found that the workability region for the AZ91 alloy powder compacts is different from that of the commercial AZ91 alloy fabricated by die casting [26], which proves that forming conditions can affect the distribution of the processing map. Compared with the bimodal sized SiCp/AZ91 composite [10], the deformation temperature corresponding to the workability region of the coarse-grained nanocomposite is higher, which may be caused by the difference in grain size.…”
Section: Resultsmentioning
confidence: 99%